Myxoid Liposarcoma of the Thigh in Early Puerperium—Rare Case Report and Narrative Review - Tomasz Machałowski; Piotr Gutowski; Edyta Zagrodnik; Aleksandra Godlewska; Katarzyna Śmieja; Oliwia Kawałek; Anna Grzymała-Figura; Sylwester Michał Ciećwież; Katarzyna Gross-Kępińska; Małgorzata Szczuko; Maciej Ziętek (Diseases)
Background: Liposarcoma (LPS) is a rare malignant tumor, but it is also one of the most common adult soft-tissue sarcomas. Myxoid liposarcoma (MLPS) accounts for 30% of all LPS cases. Diagnosis during pregnancy and the puerperium is very rarely reported, and only a few cases have been reported in the thigh. Case presentation: We report the case of a 36-year-old female patient on the 11th day of the puerperium after a cesarean section. The patient presented to the gynecology ward owing to the sudden appearance of a tumor in the medial part of her right thigh. The lesion was non-painful, mobile, soft, approximately 20 cm in diameter, and protruded above the level of the rest of the thigh surface. A suspicion of hematoma was raised. The final diagnosis was high-grade MLPS. Conclusions: An MLPS diagnosis is uncommon in female patients and even rarer during pregnancy. This case represents a novel occurrence, as the first instance in which symptoms manifested during the puerperium. Proper treatment and early detection could improve disease outcomes.